Fenomena Bencana Alam dalam Teks Mantra Pangujanan - Muhammad Heno Wijayanto; I Made Suparta (Jumantara: Jurnal Manuskrip Nusantara, 2022)
Natural disasters as natural phenomena are unavoidable in human’s life. The phenomena of natural disasters can be found in the Pangujanan text. The purpose of this study is to describe the types of natural disasters represented in the Pangujanan text and to reveal the signs or symbols of the disasters. Qualitative descriptive research method is used to reveal the types and signs of a natural disaster phenomenon. In interpreting the sign, semiotic theory is needed to present it systematically. The results of this study indicate that (1) the natural disasters depicted in the Pangujanan text are earthquakes, heavy rains, thunderbolt, hurricanes, and flash floods which are narrated based on Balinese local wisdom, (2) natural disasters in the Pangujanan text as signs have given a rise to some interpretations, namely (a) some natural disasters as results of the practice of reducing rain as narrated in the Pangujanan text, and in this case, disaster mitigation is needed, and (b) some natural disasters as forces of the practice of making rain narrated in the Pangujanan text. The conclusion that can be drawn from the results of this study is that in the past, knowledge about natural disaster phenomena was narrated in a text, and in this study, we look at natural disaster phenomena narrated through the Pangujanan text. The benefit that we can take from this study is as disaster knowledge contained in ancient manuscripts.